Ethnobiology study of Begawi traditional ceremony by Pepadun community in Buyut Ilir Village, Central Lampung, Indonesia - DIAH MARYYA ULFA; YUDIYANTO YUDIYANTO; NASRUL HAKIM; ANISATU Z. WAKHIDAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ulfa DM, Yudiyanto, Hakim N, Wakhidah AZ. 2023. Ethnobiology study of Begawi traditional ceremony by Pepadun community in Buyut Ilir Village, Central Lampung, Indonesia. Biodiversitas 24: 2768-2778. The Begawi ceremony is carried out by the people of Lampung Pepadun to obtain a traditional title. Many people do not know about plants, animals, parts of plants, parts of animals used and the meaning and philosophy contained therein. This study aimed to determine the stages of the Begawi ceremony procession of the Lampung Pepadun community in Buyut Ilir Village, Central Lampung, Indonesia, the species of plants used and the used part, the species of animals used and the used part, and the philosophy contained in the Begawi ceremony. This research is qualitative field research. Data were collected through interviews, observation and documentation. The snowball sampling method was used to select the respondents. The results showed that the stages of the ceremony consisted of peppung, cangget, ngediyo, nigel, turun mandei, musek, nikel kibau, and cakak pepadun. Twenty five species of plants from 17 families and 4 species of animals from three families are used in Begawi traditional ceremony. Plant parts used are stems, flowers, leaves, seeds, buds and fruit. The philosophy contained therein is peace, prosperity, well-being, and gratitude to God Almighty. Plant conservation efforts have been made, but no conservation efforts have been made for the animals used.